Antimicrobial Efficacy of Garcinia Cambogia Fruit Extract Against Food Borne Bacterial Pathogens, In vitro and in Chicken Meat : doi: 10.5958/2581-6616.2020.00001.8 - Bhuvana, K. S.; Mandal, P. K.; Pal, U. K.; Antony, P. X.; Kasthuri , S. (Journal of Meat Science, 2021)
The use of natural preservatives to increase the shelf-life of meat and meat products is a promising trend. The present study was done  to evaluate the efficacy of the crude extract of Garcinia cambogia fruit as natural preservative in chicken meat. The in vitro antimicrobial  efficacy of a crude extract of G. cambogia fruit against common food-borne bacterial pathogens was evaluated by agar diffusion assay.  Minced chicken was inoculated with Escherichia coli and Salmonella Typhimurium and the effect of the extract on these pathogens was  studied during storage under refrigeration. The extract was tested to evaluate its efficacy as a decontaminating agent in the form of a  dip solution. The extract of G. cambogia fruit was found to have a high in vitro antimicrobial activity against the bacterial pathogens  such as Bacillus cereus, Staphylococcus aureus, Salmonella Typhimurium, Escherichia coli, Klebsiella pneumoniae, Shigella flexneri, Pseudomonas aeruginosa  and Escherichia coli O157:H7. Both 1 and 2% extract groups significantly (P0.05) difference in antimicrobial  activity was observed between levels. The evaluation of the extract as a decontaminating agent at levels of 0.5, 1 and 1.5% (v/v solution)  revealed a significant (P
Keywords: Garcinia cambogia fruit extract; Minced chicken meat; Chicken cuts; Food borne pathogens; Decontaminating agent